Descriptions of three new species of Cossidae (Lepidoptera) from Vietnam, with an updated annotated checklist - Yakovlev, Roman V. (Zootaxa, 2014)
Forty-two species of Cossidae representing 27 genera are reported for Socialist Republic of Vietnam. Three species (Paracossus zyaung Yakovlev sp. nov., Phragmacossia laklong Yakovlev sp. nov., Butaya auko Yakovlev sp. nov.) are described as new to science. Five species (Paracossus indradit Yakovlev, 2009, P. griseatus Yakovlev, 2009, Aholcocerus ihleorum Yakovlev & Witt, 2009, Skeletophyllon puer Yakovlev, 2011, Azygophleps scalaris (Fabricius, 1775) are new country records. A brief biogegraphical overview of the Cossidae of Vietnam is given.